Ayurvedic Management of Artavakshaya w.s.r. to Polycystic Ovarian Syndrome: A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Normal menstrual cycle is a crucial physiological phenomenon for maintaining woman’s health during reproductive years. Nowadays, menstrual disarrayed are the main reasons for gynecological consultations worldwide owed to faulty dietary habits and lifestyle. Oligomenorrhea is one among all menstrual disorders with a prevalence of 13.5% in general population and is characterized by irregular, inconsistent menstrual blood flow. In Ayurveda it can be correlated with Artavakshaya due to their strong symptom equality. Prevalence of Artavakshaya is rising in present gynecological practice which may leads to terrifying sequel of infertility. In modern science, only hormonal preparations are used as treatment strategies but only offer short term symptomatic management. Methodology: A female patient of 17 years of age came to OPD of National Institute of Ayurveda, Jaipur, on 29/01/2022 with chief complaints of irregular (delayed) menses with prolonged interval of 4-5 months since last 1 year along with USG findings of Bilateral Polycystic Ovarian Disease with simple Ovarian cyst in left Ovary. In this case study, patient was treated with some oral Ayurvedic preparation for 2 consecutive cycles having Strotoshodhak, Kapha- Vatashamak, and Vataanulomaka properties. Result: Patient had her menstruation regularly with normal duration during and after treatment.